Cerebral Visual Impairment in CDKL5 Deficiency Disorder Correlates With Developmental Achievement. (October 2021) - Brock, Dylan; Fidell, Andrea; Thomas, Jacob; Juarez-Colunga, Elizabeth; Benke, Tim A.; Demarest, Scott
Cyclin-dependent kinase-like 5 (CDKL5) deficiency disorder is a rare neurodevelopmental disorder characterized by infantile-onset refractory epilepsy, profound developmental delays, and cerebral visual impairment. Although there is evidence that the presence of cerebral visual impairment in CDKL5 deficiency disorder is common, the potential impact of cerebral visual impairment severity on developmental attainment has not been explored directly. Focusing on a cohort of 46 children with CDKL5 deficiency disorder, examination features indicative of cerebral visual impairment were quantified and compared to developmental achievement. The derived cerebral visual impairment severity score was inversely correlated with developmental attainment, bolstering the supposition that cerebral visual impairment severity may provide a useful early biomarker of disease severity and prognosis. This study demonstrates the utility of a cerebral visual impairment score to better capture the range of cerebral visual impairment severity in the CDKL5 deficiency disorder population and further elucidates the interaction between cerebral visual impairment and developmental outcomes.